Exploring TPACK on prospective English teachers: Synergy among technology, pedagogy, and content - Sitorus, Nurhayati; Siagian, Beslina Afriani (Universitas Jambi, Indonesia, 2025)
Mastery of Technological Pedagogical Content Knowledge (TPACK) is a crucial aspect in improving the quality of learning for prospective English teachers in the digital era. TPACK is an integration of pedagogical, content and technology in the learning process. This study aims to analyze the level of mastery of TPACK in prospective English teachers at the Faculty of Teacher Training and Education, HKBP Nommensen University. The research method used was a descriptive qualitative approach with an instrument in the form of a questionnaire. The questionnaire consisted of 34 statement items related to TPACK. The participants in this study consisted of 18 prospective English teacher students at the Faculty of Teacher Training and Education, HKBP Nommensen University. The results showed that the mastery of Content Knowledge (CK) and Pedagogical Knowledge (PK) and Technological Knowledge (TK), Technological Pedagogical Knowledge (TPK), Pedagogical Content Knowledge (PCK), and Technological Content Knowledge (TCK) aspects were categorized as good. Furthermore, the overall mastery of TPACK on prospective English teachers is categorized as good. This finding indicates that prospective English teachers at the Faculty of Teacher Training and Education, HKBP Nommensen University have readiness to teach in a technology-based environment.